2017
DOI: 10.1615/intjmedmushrooms.v19.i6.40
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Extracellular β-Glucan Isolated from the King Oyster Mushroom Pleurotus eryngii (Agaricomycetes) and Its Sulfated Form on Signaling Molecules Involved in Innate Immunity

Abstract: The aim of this study was to determine, using murine RAW 264.7 macrophages, the immunomodulatory effect of extracellular β-glucan isolated from Pleurotus eryngii (PEBG) and its sulfated derivative (PEBG-S) on signaling molecules implicated in host innate immunity. β-Glucan was extracted and purified from the mycelial culture using optimal medium concentrations. It was then chemically converted to its sulfated form. Monosaccharide composition of β-glucan was characterized with p-aminobenzoic acid ethyl ester-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…β-Glucan is a potential immunostimulant. Many studies demonstrate that β-glucan can protect against bacterial and various other infections [35,36] by stimulating immune functions both in vitro and in vivo [37,38]. However, it is not clear whether β-glucan has immunomodulatory effects on leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…β-Glucan is a potential immunostimulant. Many studies demonstrate that β-glucan can protect against bacterial and various other infections [35,36] by stimulating immune functions both in vitro and in vivo [37,38]. However, it is not clear whether β-glucan has immunomodulatory effects on leptospirosis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Park and associates [ 11 ] have recently demonstrated that the β-glucan contents were also higher in stipes of P. eryngii , claiming that this result is probably associated with the development of the major structural compounds of cell wall in mushrooms allowing for optimal supporting effect of the cap. Since β-glucans were repetitively demonstrated in a myriad of studies [ 2 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] to induce immunostimulatory events in mammalian cells, we hypothesized that this spatial variation may also impinge on the functionality of the different parts of P. eryngii .…”
Section: Discussionmentioning
confidence: 99%
“…It was originally consumed in Europe but is now widely distributed and consumed in other parts of the world including America, Asia, and Africa [ 1 ]. The advantageous nutritional and medicinal properties exerted by P. eryngii mushrooms are mediated, at least in part, by potent bioactive constituents such as the polysaccharides fraction (glucans) and other molecules that can confer a variety of health benefits such as strong immunomodulatory effects [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2013), and hepatic structure damage (Zhang et al, 2016).Moreover,P. eryngii polysaccharides (PEPs) have been shown to possess a strong anti-inflammatory activity related to their immunomodulatory effect on macrophages (Kim et al, 2017;S. Li & Shah, 2016;Xu et al, 2016), however, there are no published reports elucidating the molecular mechanism underlying these antiinflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharide fractions have been shown to be the major biological components in P. eryngii and displayed multiple and significant functional properties such as inhibitory effects on renal cancer cells (Yang et al., 2013), hyperlipidemia and hyperglycemia (Chen, Zhang, Sha, Xu, & Wang, 2016), lipid accumulation (J. Chen et al., 2013), and hepatic structure damage (Zhang et al., 2016). Moreover, P. eryngii polysaccharides (PEPs) have been shown to possess a strong anti‐inflammatory activity related to their immunomodulatory effect on macrophages (Kim et al., 2017; S. Li & Shah, 2016; Xu et al., 2016), however, there are no published reports elucidating the molecular mechanism underlying these anti‐inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%